PLAP -CAR Tcells mediate high specific cytotoxicity against colon cancer cells - Xin Li; Robert Berahovich; Hua Zhou; Xianghong Liu; Feng Li; Shirley Xu; Yuehua Wei; Djamila Ouaret; Walter Bodmer; Lijun Wu; Vita Golubovskaya (Frontiers in Bioscience-Landmark, 2020)
Placental alkaline phosphatase, PLAP encoded by ALPP gene in humans is mainly expressed in placenta and testis, and not expressed in any other normal tissues. PLAP is overexpressed in colorectal cancers which makes it an attractive target for CAR (chimeric antigen receptor)-T cell therapy. PLAP mRNA expression was detected in 21.5% (25 out of 116) of colorectal cancer cell lines and this expression was confirmed by FACS at the protein level. In addition, IHC staining on primary colorectal cancer tumors demonstrated PLAP expression in >20% of colorectal cancer tumors. We generated mouse and humanized PLAP ScFv-CAR-T cells and demonstrated high specificity against PLAP-positive colon cancer cells using RTCA (real-time cytotoxicity assay) and IFN-gamma secretion. In addition, humanized-CAR-T cells significantly decreased Lovo xenograft tumor growth in vivo. The combination of hPLAP-CAR-T cells with PD-1, PD-L1 or LAG-3 checkpoint inhibitors significantly increased the activity of hPLAP-CAR-T cells. This study demonstrates ability of novel PLAP-CAR-T cells to kill colorectal cancers and that the extent of killing can be increased by combination with checkpoint inhibitors.